HUBUNGAN DUKUNGAN SOSIAL KELUARGA DENGAN TINGKAT KEMANDIRIAN LANSIA DI DESA TAAL TAPEN KABUPATEN BONDOWOSO - Duhita, Ratu Narendra (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2020)
Elderly is an advanced stage of a life process that will be experienced by all individuals. The aging process in the elderly tends to potentially reduce the level of independence of the elderly in carrying out daily activities. This type of research is a correlational analytic method that aims to reveal the relationship of Family Social Support with the Level of Independence of the Elderly in Taal Village RT 14, RW 04 Tapen Bondowoso Regency. correlative between variables. Data were obtained about the category of family social support with the independence of the elderly in the village of RT 14, RW 04 Tapen Bondowoso district most respondents in the category of social support with good elderly independence were 15 people (93.3%), while a small proportion of social support categories with poor elderly independence were not good as many as 2 people (10.0%). The results of the analysis of the relationship of social support with the level of independence of the elderly Spearman rho statistical test results with the help of SPSS for Windows software program, obtained the value of p = 0,000 with a significant level of 0.05 (p <0.05) so that it can be concluded that H0 is rejected which means there the relationship of family social support with the independence of the elderly. If the family's social support is good, it will affect the level of independence of the elderly and among them, the cause of the elderly's independence is due to the lack of family social support and decreased the function of all cells in the elderly.